Research and Exploitation of Security Vulnerabilities in Web Applications and Prevention Methods - Nguyen, Van Nam (Vietnam-Korea University of Information and Communication Technology, 2025)
Graduation thesis of Information Technology - Network & Information Security; 2020 - 2025